2016
DOI: 10.4049/jimmunol.1500130
|View full text |Cite
|
Sign up to set email alerts
|

Subclinical-Dose Endotoxin Sustains Low-Grade Inflammation and Exacerbates Steatohepatitis in High-Fat Diet–Fed Mice

Abstract: Subclinical circulating bacterial endotoxin lipopolysaccharide (LPS) has been implicated as an important cofactor in the development and progression of nonalcoholic steatohepatitis (NASH), but the underlying mechanisms remain unclear. Here, we demonstrated that 4-week injection with super-low dose LPS significantly promoted neutrophils infiltration and accelerated NASH progression, including exacerbated macro-vesicular steatosis, inflammation and hepatocyte ballooning in high-fat diet fed apolipoprotein E knoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 35 publications
(37 citation statements)
references
References 47 publications
0
37
0
Order By: Relevance
“…As systemic LPS injection may not only affect monocyte programming, but also other tissues such as the liver and metabolic processes2930, we further examined whether the re-programmed monocytes, instead of other systemic effects of LPS, may be causally involved in the exacerbation of atherosclerosis. To address this issue, we performed adoptive transfer experiment with in vitro programmed monocytes.…”
Section: Resultsmentioning
confidence: 99%
“…As systemic LPS injection may not only affect monocyte programming, but also other tissues such as the liver and metabolic processes2930, we further examined whether the re-programmed monocytes, instead of other systemic effects of LPS, may be causally involved in the exacerbation of atherosclerosis. To address this issue, we performed adoptive transfer experiment with in vitro programmed monocytes.…”
Section: Resultsmentioning
confidence: 99%
“…100 ng/ml (Fig. 1E), indicating that it contributes primarily to repression of macrophage responses rather than training (25,26). Time-course stimulation showed that IRAK-M mRNA was induced after 6 h, peaking at 12 and 24 h following treatment with 100 ng/ml of LPS (Fig.…”
Section: Resultsmentioning
confidence: 92%
“…Yet, we cannot rule out the involvement of others toxic compounds, particularly during NAFPD progression. Indeed, some studies suggest a possible causal relationship between NAFLD/ NAFPD-related disorders with chronic intermittent hypoxia elicited by obstructive sleep apnea [165,166], bacterial endotoxin [167][168][169], glyceraldehyde [170], methylglyoxal [171][172][173], advanced glycation end products (AGE)s [174], receptor for advanced glycation end products (RAGE) [175], nitric oxide/peroxynitrite [176], and lipid peroxidation end products [177,178].…”
Section: Discussionmentioning
confidence: 99%